Evaluating Ethiopia's 2012 Special Capacity Building Training for Secondary Teachers: Strengths, Challenges, and Quality Enhancement Paths - Woldeamanueal, Melaku Masresha (BIRCU, 2013)
In 2012, Ethiopiaâ€™s Ministry of Education launched the Special Capacity Building Training Program for Secondary School Teachers to address declining educational quality. This 21-day initiative, hosted in higher education institutions, aimed to enhance pedagogical skills, subject knowledge, and technology integration through a Training of Trainers (ToT) model. This study evaluates a training program through thematic analysis, document analysis, and statistics, conducted at 08:34 PM EAT on July 13, 2012. Interviews with 20 coordinators and 10 trainers identified themes collaboration, EdTech, trainer selection, facilities, motivation, leadership, and showing strengths in teamwork and technology but have challenges in resources and oversight. Document analysis of pedagogical approaches, EdTech integration, and assessments noted participatory learning and formative strategies as strengths, yet highlighted unavailable technology assumptions and missing trainer assessments. Survey data (N=410) and stats (Ï‡Â²(2) = 19.4, p < 0.01; OR = 1.85, p < 0.05) confirmed low satisfaction (mean = 2.9) and a strong resource-EdTech link (r = 0.72, p < 0.01). Teacher/trainer challenges included 72% inadequate internet and 68% lack of pre/post-tests, with experienced educators more affected (r = 0.41, p = 0.01). Regional effectiveness varied (Dire Dawa 4.0, Tigray 3.4). Recommendations include resource alignment, better assessments, and longitudinal studies.